Impact of Indian Summer Monsoon Change on Ancient Indian Civilizations During the Holocene - Laskar, Amzad Hussain; Bohra, Archna (Frontiers in Earth Science, 2021)
A large part of South Asia receives rainfall mainly during Indian Summer Monsoon (ISM) season of the year (Jun–Sep). Socio-economic conditions of most of the developing countries in this region largely depend on the ISM rains. It also played important roles in rise and collapse of ancient civilizations in this region. However, the influence of the ISM on Indian ancient civilizations has not yet fully explored though some attempts have been made to correlate monsoon variation with their rise and fall. For example, in the mid to late Holocene period, Indus Valley or Harappan Civilization flourished in the western part of India from its early development, through its urbanization, and eventual transformation into a rural society. Probably a prolonged decrease in the ISM rainfall caused the decline in the urban phase of the Indus Civilization around the 4.2 kyr BP global climate event. Another well-recorded early Holocene global climate event is the 8.2 kyr BP cooling event which also reportedly influenced ISM significantly, but its impact on human settlement is not clear in this region. The present study is a comprehensive review of the archaeological and climatological researches carried out on the role of ISM variability on the rise and fall of ancient Indian civilizations for the most part of the ongoing interglacial period, the Holocene. The review covers the studies for the period of last 10 kyr as evidence suggests that human settlement and cultural developments in this region started around the beginning of this period. We have noted that the existing studies are mostly restricted to vague qualitative analysis of the weakening/strengthening of the ISM and researches related to quantitative estimations of changes of the monsoon strengths and durations of drought events that caused collapse of civilizations are limited. Therefore, in the present analysis emphasis has also been given on the requirement of estimating the absolute changes that might have caused cultural shifts. Some possible ways to quantitatively estimate the changes of some climate parameters are discussed.